Hydrocephalus in Neurocysticercosis: Challenges for Clinical Practice and Basic Research Perspectives - Hamamoto Filho, Pedro Tadao [UNESP] (2019)
The objective of this paper is to discuss relevant data on the epidemiology of hydrocephalus in neurocysticercosis, the new knowledge coming from experimental studies, the pathophysiological mechanisms involved, and the controversies regarding clinical and surgical management, through a comprehensive review of the literature. Hydrocephalus is present at the onset of the disease in 16% to 51% of patients with neurocysticercosis and in 64% to 72% of patients with the extraparenchymal form of the disease. Animal models have successfully reproduced the disease and open new therapeutic approaches perspectives. Current guidelines suggest that, when hydrocephalus is due to viable cysts that can be excised surgically, cyst removal is recommended. On the other hand, degenerating cysts with protein discharge become fixed and evoke inflammation throughout the cerebrospinal fluid compartments. In these cases, surgical removal is risky, and ventriculoperitoneal shunts should be placed with close monitoring of infection and malfunction. Cysticidal treatment after shunt surgery is recommended in cases of cysts located in cerebral areas that prevent surgical management. In conclusion, mechanical obstruction and inflammation are the key pathophysiologic mechanisms in the development of neurocysticercosis-induced hydrocephalus. Anthelmintic drugs and surgical options should be used, but they have limitations. A better understanding of the disease can come from experimental models.